EVALUASI PELAKSANAAN KEGIATAN GUBERNUR BADAN EKSEKUTIF MAHASISWA PERIODE 2019/2020 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Devi Ramsah Wahyuni Simamora; Titi Maemunaty; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This research is motivated by the evaluation of the implementation of the governor's activities so that the problem formulation in this study is whether the Evaluation of the Implementation of the Activities of the Governor Executive Body of the 2019-2020 Student Period at the Faculty of Teacher Training and Education, University of Riau has been well implemented "? The benefits of this research as input material to add knowledge about the organization to students and its application in establishing cooperation among other BEM members. This research is descriptive with a quantitative approach. The population in this study was 87 people. Sampling in this study used simple random sampling. The instrument used was a questionnaire containing 47 items of statements that were valid to be used as research instruments. Data analysis through quantitative descriptive analysis. Weight each answer for Very Good (SB) with a score of 5, Good (B) with a score of 4, Fairly Good (CB) with a score of 3, Poorly (KB) with a score of 2, Not Good (TB) with a score of 1. From the findings of the study of the three indicators it can be concluded that the indicators are classified as good. This is evidenced from the presentation of the recapitulation of the Evaluation of the Implementation of the Activities of the Governor of the Student Executive Body 2019/2020 Period of the Teaching and Education Faculty of Riau University as a whole indicator: (1) comparing with the percentage of 79% then the percentage (2) contained in the indicator differentiating with a percentage of 78% and the third (3) is the indicator rate with a percentage of 76%. The meaning is the Evaluation of the Implementation of the Activities of the Governor of the Student Executive Board for the 2019/2020 Period of the Faculty of Teaching and Education at the University of Riau, which is quite good Key Words: Evaluation, Implementation, Activities